Implementasi Knowledge Management System dan Knowledge Sharing Berbasis ChatBot – Penyakit Parvo pada Anjing - I Ketut Widhi Adnyana; Jenny Octavia; Ni Kadek Ariasih (Universitas Bandar Lampung (UBL), 2021)
Canine Parvovirus is the leading cause of death for dogs, especially in puppies under six months of age. This disease is caused by the Parvovirus. Parvovirus comes from the Latin Parvus which means small. Symptoms of disease caused by CPV are characterized by vomiting and bloody diarrhea with a characteristic odor. Therefore, Parvo disease is often called Gastroenteritis in dogs. Puppies under the age of three months infected with this virus only survive 1-2 days before dying. Knowledge Management is an activity in managing Knowledge as an asset, wherein various strategies there is the distribution of the right Knowledge to the right people and quickly so that they can interact with each other, share knowledge and apply it in their daily work. with the help of a chatBot which can later help owners or veterinarians to find and provide information about diseases in animals, especially dogs, effectively and efficiently. by using the webhook method to communicate with users via social media Telegram. Webhook is a method that is installed on hosting, by using a webhook the chatBot application can communicate in real-time.